Analysis of the effect of compaction variations on the hardness of the reduced sponge iron from iron sand in South Aceh Regency - Reza Putra; Muhammad Sayuti; Muhammad Yusuf; Muhammad Muhammad; Muhammad Faisal (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Judul: Analisa pengaruh variasi kompaksi terhadap kekerasan sponge iron hasil reduksi dari pasir besi Kabupaten Aceh Selatan Title: Analysis of the effect of compaction variations on the hardness of the reduced sponge iron from iron sand, South Aceh RegencyTelah di lakukan penelitian tentang karakteristik sponge iron dari bahan baku pasir besi dan paduannya, yang berasal dari daerah Manggamat Simpang Dua kecamatan Kluet Tengah kabupaten Aceh Selatan. Sponge iron dibuat dalam bentuk pellet dengan pencampuran yang terdiri dari pasir besi (Fe) sebanyak 500 gr, karbon (C) sebanyak 2 gr, dan zat perekat sebanyak 1 gr. Pembuatan pellet terdiri dari lima variasi tekan yaitu 50 kg⁄cm2, 60 kg⁄cm2, 70 kg⁄cm2, 80 kg⁄cm2 dan 90 kg⁄cm2, yang direduksi dengan gas asitelin pada suhu pembakaran 1200℃ dengan waktu penahanan 45 menit. Hasil pengujian komposisi dengan menunjukkan kadar Fe setelah direduksi sebesar 59,38 %, dengan kadar karbon (C) 0,97% yang membentuk hematit dengan fasa Fe2O3 (besi oksida). Hasil kekerasan material sponge iron tertinggi rata-rata pada 287,35 HV pada penekanan 70 kg⁄cm2 yang menunjukkan nilai tekan (kompaksi) optimum pada pellet pasir besi. Hasil penelitian menunjukkan bahwa pasir besi yang diperoleh dari daerah Aceh selatan dapat di produksi menjadi supply bahan baku produksi baja di Aceh. The properties of sponge iron produced from iron sand and its alloys from the Manggamat Simpang Dua region in South Aceh are discussed in this research. Sponge iron is produced in pellet form by combining 75 percent iron sand (Fe), 20 percent carbon (C), and 5 percent bentonite adhesive. Pellet manufacturing consists of five press variants, namely 50, 60, 70, 80, and 90 kg/cm2, which are reduced by acetylene gas at a burning temperature of 1200°C with a holding period of 45 minutes. The reduced to spongy pellets exhibited a dominating hematite (Fe2O3) phase fraction pattern of 59.8 percent and a magnetite phase (Fe3O4) of 40.2 percent, with a weight percentage of Fe of 66.57 percent and C of 2.30 percent. The greatest sponge iron material hardness results on average at 287.35 HV at a pressure of 70 kg/cm2 with a void size of 0.4 mm, showing the optimal compressive value (compaction) on iron sand pellets. It may be inferred that iron sand collected from the South Aceh region can be used as an alternate raw material in the steel manufacturing process.